Sleep Patterns of Resident Physicians and the Effect of Heartfulness Meditation. Issue 1 (January 2021) - Thimmapuram, Jayaram; Pargament, Robert; Tredici, Sonya Del; Bell, Theodore; Yommer, Deborah; Daoud, Dana; Powell, Frankie; Madhusudhan, Divya K.
Background: Medical residents are vulnerable to poor sleep quality due to intense work shifts and academic load. Studies objectively quantified with sleep quantity and quality among resident physicians are limited. Meditation techniques have been shown to improve sleep but are rarely studied in this population. The aim of the present study is to evaluate sleep patterns of internal medicine residents and the effect of a structured Heartfulness meditation program to improve sleep quality. Methods: A total of 36 residents participated in a pre–post cohort study from January 2019 through April 2019. Sleep was monitored during a one-week outpatient rotation with two validated assessment tools, namely consensus sleep diary and actigraphy. After four intervening weeks, when the residents returned to the same rotation, Heartfulness meditation was practiced and the same parameters were measured. At the end of the study period, an anonymous qualitative feedback survey was collected to assess the feasibility of the intervention. Results: All 36 residents participated in the study (mean age 31.09 years, SD 4.87); 34 residents (94.4%) had complete pre–post data. Consensus sleep diary data showed decreased sleep onset time from 21.03 to 14.84 min ( P = .01); sleep quality and restfulness scores increased from 3.32 to 3.89 and 3.08 to 3.54, respectively ( P < .001 for both). Actigraphy showed a change in sleep onset time from 20.9 min to 14.5 min ( P = .003). Sleep efficiency improved from 83.5% to 85.6% ( P = .019). Wakefulness after initial sleep onset changed from 38.8 to 39.9 min ( P = .682). Sleep fragmentation index and the number of awakenings decreased from 6.16 to 5.46 ( P = .004) and 41.71 to 36.37 ( P = .013), respectively. Conclusions: Residents obtained nearly 7 h of sleep during outpatient rotation. Findings suggest a structured Heartfulness meditation practice to be a feasible program to improve subjective sleep onset time and several objective measures among resident physicians.